Academic lexis and disciplinary practice: corpus evidence for specificity - Hyland, Ken; Tse, Polly (International Journal of English Studies, 2009)
The presence of unfamiliar words and expressions in academic texts is a serious obstacle to students reading in a second language. EAP has responded to this challenge by taking the view that there is a common core of academic vocabulary which is frequent across an academic register. This paper briefly considers this view by examining the range, frequency, collocation, and meaning of items on the Academic Word List (AWL) in a large multidisciplinary corpus. Our corpus analysis shows that individual lexical items on the list often occur and behave in different ways across disciplines and that words commonly contribute to ‘lexical bundles’ which also reflect disciplinary preferences. Our findings question the widely held assumption that there is a single core vocabulary needed for academic study and suggests that teachers should assist students towards developing a more restricted, disciplinary-based lexical repertoire.